Field notes contributed by Paul Martsching, winter 1981-1982 - Martsching, Paulet al (1981)
Field notes were contributed by Paul Martsching. Verifying documentation of an extraordinary sighting of a Goshawk is included. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed